2007
DOI: 10.1158/1078-0432.ccr-07-0708
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Epitopes from the Wilms' Tumor 1 Oncoprotein Stimulate CD4+ and CD8+ T Cells That Recognize and Kill Human Malignant Mesothelioma Tumor Cells

Abstract: Purpose: Wilms' tumor 1protein (WT1), a transcription factor overexpressed in malignant mesothelioma, leukemias, and other solid tumors, is an ideal target for immunotherapy. WT1 class I peptide epitopes that were identified and shown to stimulate CD8+ T cells are being tested as vaccine candidates in several clinical trials. The induction and maintenance of a robust memory CD8 + cytotoxicT-cell response requires CD4 + T-cell help. Experimental Design:Three HLA class II peptide epitopes of WT1with high predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 47 publications
1
79
0
1
Order By: Relevance
“…Similar modifications have led to peptide analogues which are effective at inducing immune responses against a range of tumor types including leukemia and solid tumors [54, [57][58][59]94,95](reviewed in [96]). Despite inherent problems in demonstrating the ability of modified peptides to recognize and kill tumor cells, some heteroclitic epitopes have shown promise in phase I clinical trials [18,71,97].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar modifications have led to peptide analogues which are effective at inducing immune responses against a range of tumor types including leukemia and solid tumors [54, [57][58][59]94,95](reviewed in [96]). Despite inherent problems in demonstrating the ability of modified peptides to recognize and kill tumor cells, some heteroclitic epitopes have shown promise in phase I clinical trials [18,71,97].…”
Section: Discussionmentioning
confidence: 99%
“…Such alterations to the anchor residues can enhance peptide immunogenicity [44] and success of this strategy is dependent on the TCR binding portion of the peptide not being altered significantly by anchor residue substitution. The fact that TCR recognition exhibits a degree of cross reactivity [52] developed a WT1 CD4 + peptide epitope, 122-140, which was mutated through a substitution of residue 126 (arginine to tyrosine) [59]. The group demonstrated that native WT1 epitopes presented on the surface of human cancer cells could be recognized by CD4 + and WT1-specific CTL; which were induced in response to the peptide analogue produced through the mutation of wt peptide.…”
Section: Analogue Peptidesmentioning
confidence: 99%
“…16 Two HLA-A0201 cell lines were used as targets. The WT1-positive, ALL-derived cell line 697 was kindly provided by Hans J. Stauss (University College, London, United Kingdom), and the WT1-negative B-cell lymphoma cell line SKLY-16 was obtained from the ATCC.…”
Section: Chromium-51 Cytotoxicitymentioning
confidence: 99%
“…In addition, we developed human leukocyte antigen (HLA) class II peptides that have been shown to induce WT1-specific CD4 ϩ responses in a broad range of HLA-DR.B1 haplotypes. 16 Given the experience with disease status in allogeneic stem cell transplantation and numerous animal models, immune responses are much less probable to be effective in situations of high-volume disease. The chance for the successful application of such a modality may therefore be best when leukemia burden is minimal, so we chose to test the vaccine when patients are in complete remission (CR) but have measurable WT1 transcript.…”
Section: Introductionmentioning
confidence: 99%
“…It is known to be upregulated in epithelioid MM but not in the sarcomatoid subtype and furthermore, its expression does not appear to be of significant prognostic value (Kumar-Singh et al, 1997). However, WT-1 is a relevant immune target in MM (May et al, 2007).…”
Section: Tumour-associated Antigens In MMmentioning
confidence: 99%